SOSIALISASI SMK3RS DI RUMAH SAKIT UMUM SEMBIRING DELI TUA BERDASARKAN PP NO 50/2012 TAHUN 2023 - Anggita, Rizliana; Prima, Armanda; Septriani Br Ginting, Evfy; Siregar, Ripai; Siddiq, Muhraza (Jurnal Pengabdian Masyarakat Putri Hijau, 2025)
Occupational Health and Safety in Hospitals (K3RS) is an essential aspect of creating a safe and healthy work environment in hospitals. The effective implementation of the Hospital Occupational Health and Safety Management System (SMK3RS) can reduce the risk of workplace accidents and occupational diseases, while also improving productivity and labor efficiency. This service aims to eval_uate the implementation of SMK3RS at Rumah Sakit Umum Sembiring Deli Tua, identify the challenges faced, and provide recommendations to improve the execution of K3RS. The method used in this service is in-depth interviews with K3RS officers and analysis of work accident data at the hospital. The results show that the socialization of SMK3RS at Rumah Sakit Umum Sembiring Deli Tua is still suboptimal, with most staff not receiving adequate information regarding K3RS policies and procedures. Furthermore, monitoring and eval_uation of the SMK3RS implementation were also found to be insufficient. Therefore, this study recommends that the hospital strengthen its socialization programs, enhance training and emergency response simulations, and conduct periodic eval_uations of SMK3RS implementation to create a safer and healthier work environment